The Implementation of the Best Interest of the Child Principle in the Diversion Process of Child Investigation in Traffic Offense Cases (A Study of Way Kanan Police Resort) - Marcello, Muhammad Reuben; Manaf, Idham (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
A child, as a legal subject, holds a special status that demands distinct treatment compared to adults, both in terms of legal procedures and handling approaches. The issues in this research include how the diversion process is carried out for children as traffic crime offenders at the Way Kanan Police Department and how the principle of the best interest of the child is implemented in the diversion process at the Way Kanan Police Department. The research method used is a normative legal approach supported by an empirical legal approach. Data was collected through library research on legislation and direct interviews with investigators at the Way Kanan Police Department. The research findings show that the handling of child cases has been carried out in accordance with Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, through coordination with the prosecutor’s office and the involvement of the Correctional Center. The principle of the best interest of the child is applied by considering the fulfillment of the child's rights, protecting their psychological condition, and resolving the case through restorative justice efforts. However, in practice, there are still obstacles, such as the influence of third parties in the reconciliation process and legal issues related to parental negligence that contribute to traffic accidents. This study concludes that the application of the principle of the best interest of the child must be balanced and contextual, while also considering parental responsibility and the sense of justice for society, so that child protection goals can be achieved without neglecting legal certainty.